Determination of Tree Crown Diameters with Segmentation of a UAS-Based Canopy Height Model - Yilmaz, Volkan; Yilmaz, Serifoglu Cigdem; Tasci, Levent; Gungor, Oguz (Ipsi Belgrade Ltd, 2017)
Tree crown diameter, which is the diameter of the circle enclosing the projection of tree crown, is one of the most important stand parameters that should be identified before the production of forest management plans. This feature is generally obtained with terrestrial measurements, which may not be time-and costefficient in most cases. The use of advanced satellites and Unmanned Aerial Systems (UAS) would be of help to calculate this parameter with high accuracy. This study aims at determining the diameter of each tree crown by using a Canopy Height Model (CHM) extracted from the aerial photos acquired by a UAS. The CHM was segmented with the Multiresolution (MR) and Region Growing (RG) segmentation techniques to delineate each tree crown. The results showed that the MR and RG segmentation techniques calculated the tree crown diameters with RMSs of 1.59 m and 1.76 m, respectively.
Keywords: Tree crown diameter; image segmentation; multiresolution segmentation; region growing segmentation; unmanned aerial systems